Exploration of Some Nutrient Absorption–Related Genes and Intestinal Histology in Japanese Quails (Coturnix japonica) Throughout Their Productive Lifespan - Hamid Reza Rafieian‐Naeini; Mahdi Zhandi; Maryam Taghipour‐Shahbandi; Amir Reza Sabzian; Ali Reza Yousefi; Mahboubeh Khajehnabi; Woo Kyun Kim (Veterinary Medicine and Science)
ABSTRACT Background Quail is an efficient poultry species known for many years, and its productivity is highly affected by gastrointestinal function, health, digestion and commensal bacteria. Specific histological parameters and nutrient absorption–related genes could be used to study intestinal functionality and efficiency. Objectives This study aimed to evaluate the mRNA abundance of nutrient absorption–related genes and intestinal histology changes in laying Japanese quail during productive lifespan. Methods A total of 135 quails from a commercial flock at different egg production periods (early production [EP, 6 weeks of age], pick production [PP, 21 weeks of age] and post pick production [PPP, 40 weeks of age]) were randomly selected (n = 45/group) and kept for 6 weeks. Production performance was evaluated during last 2 weeks of the experimental period, and tissue samples were taken from the duodenum, jejunum and ileum for histological analysis and mRNA abundance purposes at the end of the experiment. The mRNA abundance of the CALB1, SGLT1, SGLT5, EAAT3 and NaPi‐IIb genes were compared among groups. Results Production period did not affect the eggshell thickness, goblet cell number and mRNA abundance of CALB1, EAAT3 and NaPi‐IIb (p > 0.05). The PPP quails had the highest egg weight and FCR compared to EP and PP quails (p < 0.001). Egg production and egg mass of the EP and PP quails were higher than those of PPP quails (p < 0.001). Moreover, EP quails had the highest villus height (VH)/crypt depth (CD) ratio in the duodenum and jejunum and the lowest VH:CD in the ileum compared with the PPP quails (p < 0.01). The lowest SGLT1 mRNA abundance was noted in the PP quails, whereas EP quails had the highest SGLT5 mRNA abundance (p < 0.05). Conclusions In conclusion, although histology parameter changes were in‐line with the lowest performance observed in the PPP quails, the current results failed to show a relationship between mRNA abundance changes and production performance attributes at different productive lifespans.